Utility of Ultrasonography in Assessing the Effectiveness of Extracorporeal Shock Wave Therapy in Insertional Achilles Tendinopathy - Cheng, Yi (Biomed Res Int, 2016)
Introduction. The aim of this study was to investigate the utility of ultrasonography (US) for predicting and assessing the effectiveness of extracorporeal shock wave therapy (ESWT) in insertional Achilles tendinopathy (IAT). Methods. A total of 42 patients with an established diagnosis of chronic IAT were examined by US before ESWT and at 4 weeks and 12 weeks after ESWT. The thickness and cross-sectional area (CSA) of the Achilles tendon, size of calcific plaques, tendon structure score, and neovascularization score were measured at each time point. Results. After therapy, Victorian Institute of Sport Assessment-Achilles (VISA-A) scores increased significantly, and the size of calcific plaques decreased (P < 0.05). Neovascularization scores increased at the 4th week and then decreased at the 12th week (P < 0.05). The thickness, CSA, and structure of the Achilles tendon did not change. Variables observed by US at baseline were not associated with changes in VISA-A scores at follow-up. However, the changes in calcific plaque size and neovascularization scores were related to the improvement of VISA-A scores between pre- and posttherapy (P < 0.01). Conclusion. Ultrasonography can reveal some changes in the insertion of the Achilles tendon after ESWT, but the outcome of ESWT in IAT cannot be predicted by the variables observed by US.